Simplifikasi Pengawasan Barang Ekspor Dalam Rangka Penegakan Hukum Kepabeanan - Rahim, Asri; Darwis, Muhammad; Natsir, Muhammad (Jurnal Litigasi Amsir, 2023)
This study aims to determine the supervision of export activities at the Parepare Customs and Excise Office. And to find out the efforts of the Parepare Customs and Excise Office in enforcing the law on violations of export activities. The type of research used in this research is empirical normative research. they are supported by a statutory approach and a structural approach. The study results in show that supervision of export activities at the Parepare Customs and Excise Office is carried out administratively and physically, starting from the arrival of the means of transport, loading of exported goods, and administrative services for completeness of export documents. The Parepare Customs and Excise Office made efforts to enforce the law on violations of export activities by analyzing export documents and collecting information on the vulnerability of illegal exports so that during the research period no legal violations were found in export activities.